2000
DOI: 10.1038/35002032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imprinting of bulk, microporous silica

Abstract: Molecular imprinting aims to create solid materials containing chemical functionalities that are spatially organized by covalent or non-covalent interactions with imprint (or template) molecules during the synthesis process. Subsequent removal of the imprint molecules leaves behind designed sites for the recognition of small molecules, making the material ideally suited for applications such as separations, chemical sensing and catalysis. Until now, the molecular imprinting of bulk polymers and polymer and sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
307
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(312 citation statements)
references
References 18 publications
3
307
0
2
Order By: Relevance
“…Multiple-point covalent imprinting has been employed to form pairs or triplets of identical functional groups within a silica matrix. The catalysts reported by Katz and Davis 38 illustrate this approach. Different molecular templates were prepared incorporating carbamate-protected amine groups and triethoxysilyl groups.…”
Section: Imprintingmentioning
confidence: 93%
“…Multiple-point covalent imprinting has been employed to form pairs or triplets of identical functional groups within a silica matrix. The catalysts reported by Katz and Davis 38 illustrate this approach. Different molecular templates were prepared incorporating carbamate-protected amine groups and triethoxysilyl groups.…”
Section: Imprintingmentioning
confidence: 93%
“…It is based on the formation of a supramolecular complex of organic monomers together with a template molecule before polymerization. This procedure enables the threedimensional positioning of the recognition units in the produced organic polymer 15,16 . Inorganic molecularly imprinted materials have also been developed.…”
mentioning
confidence: 99%
“…Inorganic molecularly imprinted materials have also been developed. For instance, Katz and David 15 reported on the imprinting of bulk microporous silica. The originality of their approach lies on the choice of a building block that was used to occupy the micropores and to attach the functional groups to the walls of those pores.…”
mentioning
confidence: 99%
“…Traditionally, molecular imprinted polymers (MIPs) are prepared in the form of bulk monoliths. Davis et al first reported the imprinting of bulk amorphous silica [1]. The major drawback associated with the imprinted material was the difficult diffusion of adsorbents to imprinted sites.…”
Section: Introductionmentioning
confidence: 99%